Secretion of phospholipase C by Pseudomonas aeruginosa. - Stinson, M W (1979)
The conditions necessary for the secretion of phospholipase C (phosphatidylcholine cholinephosphohydrolase) by Pseudomonas aeruginosa were studied. Enzyme secretion by washed cell suspensions required a carbon source and ammonium, potassium, and calcium ions. The calcium requirement could be substituted by magnesium and strontium but not by copper, manganese, cobalt, or zinc. During growth in liquid medium, cells secreted phospholipase C during late logarithmic and early stationary phases. Secretion was repressed by the addition of inorganic phosphate but not by organic phosphates, glucose, or sodium succinate. Studies with tetracycline indicated that de novo protein synthesis was necessary for the secretion of phospholipase C and that the exoenzyme was not released from a preformed periplasmic pool. Similarly, extraction of actively secreting cells with 0.2 M MgCl2 at pH 8.4 solubilized large quantities of the periplasmic enzyme alkaline phosphatase but insignificant amounts of phospholipase C. Bacteria continued to secrete enzyme for nearly 45 min after the addition of inorganic phosphate or rifampin.